Environmental effect on the performance of passive daytime photonic radiative cooling and building energy-saving potential - Bijarniya J.P.; Sarkar J.; Maiti P. (My University, 2025)
Passive photonic radiative cooling is used to make sky exposed surfaces sub-ambient with recent development in metamaterials throughout the day and night cycle. Daytime radiative cooling depends on the intensity of solar radiation, and both daytime and nighttime radiative coolings have a function of environmental factors like ambient temperature, humidity, wind velocity, cloud fraction, etc. Hence, the passive radiative coolers have location-specific performance and need analysis individually for a location before implementation. In this paper, the potential of passive radiative cooling for Indian cities of various climatic conditions covering maximum climate diversity is evaluated for different (ideal, broadband and selective) emissive radiative cooler surfaces. The effects of various environmental parameters on the cooler performance are studied. The cooling energy-saving potentials of various photonic radiative coolers as roof envelope integrated with the conventional air conditioning system are evaluated as well. Results reveal that the selective radiative cooler performs better in low humidity locations, namely Jaisalmer and Delhi, with maximum temperature drops of 20.6 °C and 17.3 °C, respectively. However, it is less likely to recommend for monsoon season and high humid cities. The cooling load reduction of 36% observed for low humidity locations with an integrated system. © 2020 Elsevier Ltd